Chiral derivatives of xanthones and benzophenones: Synthesis, enantioseparation, molecular docking, and tumor cell growth inhibition studies. Issue 4 (15th January 2021) - Phyo, Ye' Zaw; Teixeira, Joana; Gonçalves, Ricardo; Palmeira, Andreia; Tiritan, Maria Elizabeth; Bousbaa, Hassan; Pinto, Madalena M.M.; Fernandes, Carla; Kijjoa, Anake
Abstract : Abstract: Liquid chromatography enantioseparation and determination of enantiomeric purity of synthetized xanthone and benzophenone derivatives comprising one or more chiral moieties are reported. High enantioselectivity and resolution were observed in ( S, S )‐Whelk‐O1 chiral stationary phase (CSP) for the enantiomeric mixtures of compounds comprising an aromatic ring linked to the stereogenic center(s), with α values ranging from 1.35 to 4.15 and Rs values ranging from 2.22 to 13.87. Among all the tested enantiomeric mixtures, those comprising three chiral moieties positioned in the xanthone scaffold gave the best chromatographic results. Enantiomers comprising an alkyl chain linked to the stereogenic centers were enantioseparated on a Lux® Celullose‐2 CSP. For both CSPs, the elution was performed in polar organic mode. The enantiomeric ratio (e.r.) values were always higher than 99%. Additionally, assessment of chiral recognition mechanisms on ( S, S )‐Whelk‐O1 CSP was performed by molecular docking approach, which are in accordance with the chromatographic parameters. The nature and number of chiral moieties in the central aromatic scaffold of either xanthone or benzophenone derivatives are proved to be crucial for enantiorecognition. The evaluation of the growth inhibition of human tumor cell lines revealed that ( S, S )‐(+)‐5 was the most potent compound, with values of GI50 of 12.83 ± 2.09 μM for A375‐C5 melanoma, 12.40 ± 1.16 μM for MCF‐7 breast adenocarcinoma, and 13.06 ± 1.29 μM for NCI‐H460 non‐small cell lung cancer. In some cases, the growth inhibitory effects demonstrated to be dependent on the stereochemistry of the compounds.